No-tillage combined with deficit irrigation improves canopy photosynthesis and water use efficiency to stabilize yield in intercropped maize - Guo, Congcong; Wang, Yan; Bao, Xiaoyuan; Fan, Hong; Sun, Yali; He, Wei; Cui, Fuyang; Bai, Chengxin; Li, Xinying; Zhao, Cai (Frontiers in Plant Science, 2026)
IntroductionWater scarcity and uneven distribution of irrigation resources are major challenges for sustaining maize production in arid agro-ecosystems. While intercropping and conservation tillage have been individually recognized for enhancing crop productivity and resource efficiency, their integrated effects with irrigation management remain poorly understood. The long-term field platform was launched in 2015, and the trial was conducted in the northwest region in 2024, we embedded a three-factor split-plot experiment to evaluate the combined impacts of tillage (no-tillage, NT; conventional tillage, CT), planting pattern (maize–pea intercropping, IM; sole maize, SM), and irrigation regime (low, I1; medium, I2; high, I3) on maize yield, canopy photosynthetic dynamics, water-use efficiency, and photosynthetic enzyme gene expression.MethodsNo-tillage intercropping under medium irrigation (NTIMI2) consistently achieved the highest yield, exceeding CTIMI2 and NTSMI2 by 10.5% and 27.2%, respectively, mainly through increases in ear number and thousand-kernel weight. Canopylevel analyses revealed that NTIMI2 sustained higher leaf area index, leaf area duration, crop growth rate, and net assimilation rate during silking–filling, thereby extending the photosynthetic functional period. These physiological advantages translated into greater assimilate supply and efficient partitioning, supported biochemically by the upregulation of nadp-mdh and nadp-me expression during grain filling. Importantly, NTIMI2 optimized the yield–water relationship: water-use efficiency was maximized and comparable yields were maintained relative to high irrigation, but with reduced water input.DiscussionOur findings provide mechanistic evidence that coordinated tillage and irrigation strategies regulate canopy source–sink dynamics and enzyme-mediated carbon assimilation, thereby reconciling the trade-off between yield stability and water conservation. This study highlights no-tillage intercropping with medium irrigation as a scalable pathway toward climate-resilient and water-efficient maize production in arid regions.